Development of Novel Micronutrient Rich Drumstick (Moringa oleifera) Pod Pulp Chutney and Its Shelf Life Prediction - , Amee Ravani, S V Anadani, P A Shah, J Gondaliya, S H Akbari, R V Prasad (Archives of Current Research International, 2024)
Novel micronutrient rich Drumstick (Moringa oleifera) pod pulp chutney was developed and the level of ingredients were optimized. The effects of moringa pulp, coriander leaves, mint leaves and xanthan gum on textural and sensory characteristics of chutney was studied. Central composite design of Response surface methodology was adopted for designing the experiments. Quality parameters like chemical composition and nutritional parameters of optimized chutney were estimated. The optimized chutney was analyzed for accelerated storage study. The shelf life of drumstick chutney is 137 days at 7oC and 83 days at 30oC.